(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT The overall importance is focused on clarifying the knowledge of the scientific truth of the Qur’anic texts, managing their meanings, knowing the related words to the word in the Qur’anic verses, clarifying the scientific truth of the word contained in the Qur’anic texts, and distinguishing between the higher word, the lower word, the remaining word, and the word piety. There are axes to guide people, and it is difficult to go through them and manage all of them, so I addressed an important aspect of this great book, and this aspect relates to its good words that I chose to be the title of my research entitled (the term of the word and its significance in the Holy Qur’an - an objective study). Since research in such a topic required an extensive study, so I thought it appropriate to limit this study to some Qur’anic verses in which came the word and its significance.